Influence of Physical Environmental Factors on The Rising Insecurity in Northwestern Nigeria - Abdulrahim Umar Darma (Indonesian Journal of Earth Sciences, 2021)
Northern part of Nigeria has witnessed a widespread security challenges in recent years, in most cases armed conflicts. Boko Haram's insurgency in the Northeast, herdsmen militancy in North-central, while in the Northwest, banditry has become the major security concern. Millions of people have been displaced, some were dead as a result. There are efforts by concerned entities, less attention was given to physical environmental. Environmental psychology has shown that the physical environment is responsible for behavior or crime; therefore, this study identifies the environmental factors that are influencing the increase of insecurity activities in the Northwestern states of Nigeria. Data was collected using focus group discussions, observations, interviews and review of related existing literature. System theory was used to show the interdependence of the factors by identifying and categorizing them into internal and external factors (artificial and natural). The internal factors include; Urbanization and Poor Environmental Design/Planning, Territorial encroachment, Urban poverty among others. While the external factors are; Climate, Topography and Vegetation, Natural resources and etc. The study discusses their effects on increasing insecurity in the region and concluded that both internal and external factors have significant effects on the increasing banditry in Northwestern part of the country and need to be viewed as a system and be treated holistically. Finally made some recommendation on the way forward.